Awareness and readiness of 5G technology implementation in construction industry - Shafie, Muhammad Syazwi (2020)
Technological advancement and rapid economic growth have created a wide range of advanced technologies all over the time. The borderless world that used to be just described as impossible, has now become the heart and soul of the nation's driving force in various fields. Lately, issues related to 5G have often been mentioned. Its impacts were so drastic that it tends to give result of advantage and disadvantage. Today, construction industry was trying to implement the technology of 5G in construction process. Thus, this study was conducted to identify either construction player’s aware or ready to absorb the new technology. The methodologies used in this study are by using literature review and distribution of questionnaires. Data has been collected from all construction player’s that involved with the JKR Perak projects in 2019. Results of the study will show the level of awareness, readiness and advance knowledge among the construction players. The study will also provide information about the implication of using 5G technology to create big changes in reality of construction industry. Data from the study shows that the level of awareness and readiness of construction players towards new technology, especially 5G technology, is still unsatisfactory. This is driven by the factor of utilizing experts in operating 5G technology which will cost a lot of money on managing a project. Data on recent technological advances also shows that construction players are still adopting conventional technology and it is difficult to accept new changes in management and construction systems. Hopefully, the findings from this study will allow the construction players to move through the new advanced technology, thus affect the progress and increase safety in construction sites. It is also expected to provide effective suggestions on the application of 5G technology to the construction sector thus accelerate the process of managing and implementing projects without any physical weaknesses such as communication problems among construction player’s and delays in the construction process.